Myeloid-specific blockade of notch signaling alleviates dopaminergic neurodegeneration in Parkinson’s disease by dominantly regulating resident microglia activation through NF-κB signaling - Shi-Qian Liang; Peng-Hui Li; Peng-Hui Li; Yi-Yang Hu; Jun-Long Zhao; Fang-Ze Shao; Fang Kuang; Kai-Xi Ren; Tiao-Xia Wei; Fan Fan; Lei Feng; Hua Han; et al. (Frontiers in Immunology, 2023)
Yolk sac–derived microglia and peripheral monocyte–derived macrophages play a key role during Parkinson’s disease (PD) progression. However, the regulatory mechanism of microglia/macrophage activation and function in PD pathogenesis remains unclear. Recombination signal–binding protein Jκ (RBP-J)–mediated Notch signaling regulates macrophage development and activation. In this study, with an 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) hydrochloride-induced acute murine PD model, we found that Notch signaling was activated in amoeboid microglia accompanied by a decrease in tyrosine hydroxylase (TH)–positive neurons. Furthermore, using myeloid-specific RBP-J knockout (RBP-JcKO) mice combined with a PD model, our results showed that myeloid-specific disruption of RBP-J alleviated dopaminergic neurodegeneration and improved locomotor activity. Fluorescence-activated cell sorting (FACS) analysis showed that the number of infiltrated inflammatory macrophages and activated major histocompatibility complex (MHC) II+ microglia decreased in RBP-JcKO mice compared with control mice. Moreover, to block monocyte recruitment by using chemokine (C-C motif) receptor 2 (CCR2) knockout mice, the effect of RBP-J deficiency on dopaminergic neurodegeneration was not affected, indicating that Notch signaling might regulate neuroinflammation independent of CCR2+ monocyte infiltration. Notably, when microglia were depleted with the PLX5622 formulated diet, we found that myeloid-specific RBP-J knockout resulted in more TH+ neurons and fewer activated microglia. Ex vitro experiments demonstrated that RBP-J deficiency in microglia might reduce inflammatory factor secretion, TH+ neuron apoptosis, and p65 nuclear translocation. Collectively, our study first revealed that RBP-J–mediated Notch signaling might participate in PD progression by mainly regulating microglia activation through nuclear factor kappa-B (NF-κB) signaling.